PENGARUH PELATIHAN DAN SISTEM KONTROL TERHADAP PERILAKU KARYAWAN SERTA DAMPAKNYA TERHADAP KINERJA RUMAH SAKIT - Putu Karleni; Wasis Budiarto; Mei Indrawati (Prodi Magister Manajemen Universitas Wijaya Putra, 2017)
The hospital is an integral part of the overall healthcare system serving patients with different types of services that had the task of implementing the health effort in succeeded to by giving priority to curative and rehabilitative efforts undertaken in harmony and integrated with promotif and preventive efforts. The method of the research is an explanatory research, and the approach used is quantitative. The scope of human resource management is about the influence of training control system on behavior and its impact on employees performance. The sample in this study is 100 employees Darmo Hospital Surabaya. Based on the description of the respondents against the research questionnaire, that there are 35,66 % of Darmo Hospital Surabaya employee performance is still bellow standard. The training and system control influence the behavior of employees, the employees behavoir have an effect on e is significantly to employees performance, the training and system control have on significant effect to the employees performance. The training and system control are through employee behavoir have an significantly effect to employees performance.